Optimal Forest Management when Logging Damages and Costs Differ between Logging Practices - Yonky Indrajaya; Edwin van der Werf; Ekko van Ierland; Frits Mohren (Center for Economic Studies and ifo Institute (CESifo), 2014)
Papers on optimal harvesting regimes for maximizing land expectation value (LEV) that compare different logging practices often ignore differences in variable costs and in damages on the residual stand between logging practices. We use data on a multi-age, multi-species forest in East-Kalimantan to study optimal harvest regimes for Conventional Logging (CL) and for Reduced Impact Logging (RIL). We simulate a range of carbon prices with compensation for additional carbon stored under sustainable forest management (RIL). According to our detailed data, RIL has higher fixed costs but lower variable costs than CL, and leads to less damages on the residual stand. We show that when these differences are taken into account, RIL leads to highest LEV for low to intermediate carbon prices, while for high carbon prices conventional logging is preferred. Conventional logging, however, does not qualify for carbon payments. Furthermore, we show that ignoring damages in the model leads to vast overestimations of LEV and large underestimations of optimal cutting cycles for all carbon prices, and to a different choice of logging practice for low and high carbon prices. Ignoring differences in variable costs between CL and RIL leads to small overestimations of LEV for low carbon prices and small underestimations of LEV for high carbon prices, with small to zero differences in optimal cutting cycles.
Keywords: Q23; Q57; 330; sustainable forest management; reduced impact logging; optimal forest management; REDD; carbon price